(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2024)
Consumerism is reflected in the abusive acquisition of products, which are not always necessary to meet the vital needs of the human being. Today people have at their disposal all kinds of products and goods to satisfy their needs, from the most basic to the most sophisticated. However, this apparent benefit is a double-edged sword, since excessive consumption by a minority part of the world population is leading to a deficit of resources. For this reason, in recent years it has become necessary to study how we consume and what effects this fact has on the environment and society.